2023
DOI: 10.3389/fimmu.2022.1064203
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of diagnostic, prognostic, and risk blood and urine biomarkers of transplant-associated thrombotic microangiopathy

Abstract: Transplant-associated thrombotic microangiopathy (TA-TMA) is an increasingly recognized complication of allogeneic and autologous hematopoietic cellular therapy (HCT), associated with significant morbidity and mortality. Although the central drivers of the disease are thought to be endothelial damage and complement activation, no specific diagnostic biomarkers have been identified. TA-TMA is typically diagnosed using criteria comprised of non-specific clinical and laboratory features. Some patients will have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Both SOS and TA‐TMA are early disorders of endothelial dysfunction after HCT; the main difference between diseases is the location of the vessels involved (liver versus other organs, respectively). Multiple groups have suggested that SOS and TA‐TMA are thus in the same spectrum of endothelial disease 26–28 . We hypothesize that concurrent TA‐TMA and SOS reflects significant endothelial injury from myeloablative preparative regimens and may reflect severe endothelial injury unable to be reversed despite dual therapy, as 8/10 of our cohort were treated with both defibrotide and eculizumab with poor response.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Both SOS and TA‐TMA are early disorders of endothelial dysfunction after HCT; the main difference between diseases is the location of the vessels involved (liver versus other organs, respectively). Multiple groups have suggested that SOS and TA‐TMA are thus in the same spectrum of endothelial disease 26–28 . We hypothesize that concurrent TA‐TMA and SOS reflects significant endothelial injury from myeloablative preparative regimens and may reflect severe endothelial injury unable to be reversed despite dual therapy, as 8/10 of our cohort were treated with both defibrotide and eculizumab with poor response.…”
Section: Discussionmentioning
confidence: 83%
“…Multiple groups have suggested that SOS and TA-TMA are thus in the same spectrum of endothelial disease. [26][27][28] We hypothesize that concurrent TA-TMA and SOS reflects significant endothelial injury from myeloablative preparative regimens and may reflect severe endothelial injury unable to be reversed despite dual therapy, as 8/10 of our cohort were treated with both defibrotide and eculizumab with poor response. Our cohort permitted evaluation of a biologic interaction with SOS in part because this was a common complication in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a lack of standardized laboratory parameters that specifically address endothelial dysfunction in these patients. The EASIX score, which is based on the calculation of LDH multiplied by Cr, divided by platelet count, has emerged as a potential prognostic biomarker of endothelial dysfunction in patients with HSCT-TMA and GVHD [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time there are differences in TMA presentation between pediatric and adult patients. Recently published consensus aims to harmonize definitions, but specific diagnostic and prognostic biomarkers still need validation [43,44]. The drugs which target complement demonstrated potential in HSCT-TMA treatment but there are still no approved therapies.…”
Section: Hsct-associated Trombotic Microangiopathymentioning
confidence: 99%